Le Pâturage, C’est toute une science ! - Roturier, Samuel; Roué, Marie (Techniques & culture, 2016)
In Swedish Lapland, Sami reindeer breeders must now share their territory with the forest industry. Until recently, the resulting conflict was focused on lichens, which constitute the main food source for the reindeer herds during the five months of northern winter. Our analysis shows that neither the presence nor the abundance of lichen is sufficient to define pasture as represented by the herders. The Sami semantic category, guohtom, describes pasture not in its essence, but in relation to its accessibility at the time that the speaker expresses himself. By taking the access to lichen through the snow cover into account, the herders’ science consists of analyzing the many interactions between the vegetation, the snow, the climate and the environment that produces or destroys the pasture from one day to the next. This ecological knowledge allows Sami herders to control and guide the reindeer over the taiga. Throughout the winter, they assess the changes in the state of the pasture, plan the movement of their reindeer and develop land-use strategies. Pasture science is also the outcome of the ability of the herders to think like reindeer. More than ecological and technical know-how, the pasture then becomes a state of balance in space and in time, where the desires of the breeders are synchronized with the needs of the animals. En Laponie suédoise, les Samis éleveurs de rennes doivent aujourd’hui partager leur territoire avec l’industrie forestière. Le conflit qui en résulte a, jusqu’à présent, porté l’attention sur les lichens, qui constituent l’alimentation principale des troupeaux pendant les 5 mois de l’hiver boréal. Notre analyse montre que ni la présence ni l’abondance du lichen ne suffisent pourtant à définir le pâturage tel que les éleveurs se le représentent. La catégorie sémantique samie, guohtom, définit le pâturage, non pas de manière essentialiste, mais par rapport à son accessibilité à un moment donné. En prenant en compte l’accès au lichen à travers le manteau neigeux, la science des éleveurs ...